Diminutives in anthroponyms of kazakh and turkish languages (Journal of Oriental Studies, 2018)
This article describes the insufficiently explored subject in linguisticsTurkic languages – diminutive and their application in anthroponyms Kazakhand Turkish languages. Provide explanations on the terms diminutiveand anthroponyms. On examples in the Kazakh and Turkish individuallyanalyzed diminutive affixes. The test question is one of the insufficientlyknown until now the actual fact as a separate category in the diminutivegeneral linguistics, including in Turkic studies.